Decoding Masculinity: An Analysis of Stuart Hall’s Reception Theory in BTS Music Videos and Its Impact of Consuming Buying on Indonesian Fans (2013–2021) - Hasna Sofia; Nurnisya Frizki Yulianti; Sofian Muhammad Raqib Bin Mohd (SHS Web of Conferences)
This study employs the Stuart Hall model to analyse masculinity representations in BTS music videos from 2013 to 2021, examining their impact on the purchasing behaviours of the band’s predominantly female Indonesian fanbase. Through qualitative analysis involving five female fans, the research focuses on their perceptions of BTS’s videos, especially from their debut until the latest release before their conscription. Despite the assumption that female fans significantly drive sales through impulsive purchases in support of their idols, findings reveal that the varied masculinities portrayed do not substantially influence their buying decisions. Instead, these decisions are needs-based, indicating a pragmatic approach to consumerism. This research contributes to discussions on media influence, gender representation, and consumer culture, challenging the prevailing belief that fan purchasing is mainly driven by media portrayals and idol loyalty. It underscores the complex interplay of fan engagement and economic contribution in global pop culture, offering new insights into the dynamics of media consumption and fan behaviour.